PENGGUNAAN MODEL PEMBELAJARAN FLIPPED CLASSROOM UNTUK PEMBELAJARAN DARING SOSIOLOGI DI MASA PANDEMI COVID-19 KELAS X.IPS SMA NEGERI 1 JUWANA KAB. PATI TAHUN 2020 - Suharno, Suharno (IJTIMAIYA: Journal of Social Science and Teaching, 2020)
Government policies to implement online learning during the covid pandemic 19 caused many problems in schools; that is, lack of effectiveness on learning communication, students boredom, too much teacher assignments, and complaints about quota and internet networks. In this emergency situation, teachers must act quickly so that learning can run effectively. The cell phone which was originally only used as a communication media, has now become multifunctional. It is now used to provide learning material and assignments in a very short duration. The flipped classroom learning model is learning that combines learning in the classroom with learning outside the classroom with the aim of maximizing learning activities. Learning activities that are usually done in class, are now done at home. The problem in this study is " Can the use of the flipped classroom learning model in online learning Sociology be effective in increasing the competence of class X students. IPS SMA Negeri 1 Juwana in exploring, interpreting, summarizing data and creating concepts as well as creating ways of solving problems in everyday life?" This research was conducted using a class action research approach (CAR). The results of this study indicate that (1) the learning achievements of SMA 1 Juwana students in Sociology subjects can be improved through the use of a flipped classroom learning model; (2) the integration of this learning model can be done by: students (a) are given a general explanation on how to join the class in the google classroom application; (b) fill out an online attendance list individually; (c) learn the topic of the material themselves which usually uses video lessons or ppt made by the teacher; (d) independently then try to apply knowledge by solving problems and doing practical work. Flipped classroom learning is very efficient, because students are asked to study material at home, while in the Google classroom group, students can focus more on their difficulties in understanding the material or their ability to solve questions related to the material; (2) the use of the flipped classroom learning model and the integrated CTL approach can improve the cognitive competence of students in learning Sociology not only to the level of C1, C2 and C3, but also to the level of analysis, synthesis and evaluation of the concepts and generalizations they formulated.